Investigation of Effects of Thermal Radiation, Magnetic Field, Eckert Number, and Thermal Slip on MHD Hiemenz Flow by Optimal Homotopy Asymptotic Method - Solomon Bati Kejela; Mitiku Daba; Abebe Girum (Journal of Mathematics)
Analytical investigation of thermal radiation, Prandtl number, Eckert number, permeability parameter, magnetic field, velocity, and thermal slip effects on magnetohydrodynamic Hiemenz flow over a permeable plate with forced convection has been presented. Similarity variable conversion method has been applied to transmute the fundamental governing equations of the fluid dynamics in flow into a pair of nonlinear third-order ordinary differential equations and is analytically solved by the optimal homotopy asymptotic method (OHAM). The influences of several relevant physical parameters in the model on velocity and temperature of the fluid have been studied and analysed profoundly by use of graphs and tables. It is detected that, with mounting value of suction/blowing parameter and magnetic field parameter, the skin friction coefficient enhances. Likewise, it is seen that the Nusselt number increases with enhancing value of magnetic parameter. It is also witnessed that the velocity increases as the Eckert number, blowing/suction parameter, and permeability parameter increase, but it decays against magnetic field and velocity slip parameter. Moreover, the result reveals that the fluid temperature upsurges along with snowballing the radiant heat, magnetic field parameter, and the Eckert number. However, it descends against thermal slip parameter, Prandtl number, wall temperature exponent, and velocity slip parameter. A comparison with previous studies has been made, and the result shows an excellent agreement.